2015
DOI: 10.1016/j.aim.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

New restriction estimates for the 3-d paraboloid over finite fields

Abstract: We improve the range of exponents for the restriction problem for the 3-d paraboloid over finite fields. The key new ingredient is a variant of the Bourgain-Katz-Tao finite field incidence theorem derived from sum-product estimates. In prime order fields, we give an explicit relationship between the exponent in this incidence theorem and restriction estimates for the paraboloid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 18 publications
0
46
0
Order By: Relevance
“…In [8], [4] after applying the Hölder inequality the spherical average estimate was converted to an additive energy estimate on the sphere (which was trivial as the sphere was S 1 t ). It is easy to show -see (18) and (29) below -that if the set A lies on the discrete paraboloid or sphere, then (up to a permutation of vertices) the energy equals, respectively, the number of rectangles formed in F d−1 by the horizontal projections of the points x, y, z, u on the paraboloid or the rectangles with vertices x, y, z, u on the sphere in F d . We always assume that x, y, z, u in (16) are pair-wise distinct, for alternative scenarios contribute merely O(|A| 2 ) to the energy.…”
Section: Additive Energy On Quadricsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [8], [4] after applying the Hölder inequality the spherical average estimate was converted to an additive energy estimate on the sphere (which was trivial as the sphere was S 1 t ). It is easy to show -see (18) and (29) below -that if the set A lies on the discrete paraboloid or sphere, then (up to a permutation of vertices) the energy equals, respectively, the number of rectangles formed in F d−1 by the horizontal projections of the points x, y, z, u on the paraboloid or the rectangles with vertices x, y, z, u on the sphere in F d . We always assume that x, y, z, u in (16) are pair-wise distinct, for alternative scenarios contribute merely O(|A| 2 ) to the energy.…”
Section: Additive Energy On Quadricsmentioning
confidence: 99%
“…We always assume that x, y, z, u in (16) are pair-wise distinct, for alternative scenarios contribute merely O(|A| 2 ) to the energy. By a rectangle we mean a point quadruple, such that the dot products of adjacent difference vectors is zero at every vertex x, y, z, u -see (18), (29). The concept of adjacent vertices arises after rearranging equation (16).…”
Section: Additive Energy On Quadricsmentioning
confidence: 99%
“…In even dimensions the Stein-Tomas result was improved by the first two authors [8] in 2008 to R * (2 → r) 1 for r > 2d 2 d 2 −2d+2 , with the endpoint r = 2d 2 d 2 −2d+2 obtained in [15]. The second author [12] recently improved this to r > 6d+8 3d−2 for d ≥ 6, using, in part, ideas from [13]. Here we further improve these results in d ≥ 4 obtaining the optimal L 2 based results for even d ≥ 8.…”
Section: Introductionmentioning
confidence: 95%
“…In the paraboloid case, we will see that (proof of Theorem 1.16), there is a connection between the L 2 → L r estimate and the additive energy bound. In the finite field setting, such a connection was initially given by Mockenhaupt and Tao [42], and a more precise relation between them was found by Lewko [44]. However, it seems that there is no such link for the case of spheres.…”
Section: Extension Theoremsmentioning
confidence: 98%
“…This result has been improved slightly over recent years. For instance, Lewko [44] showed that there exists ǫ > 0 such that…”
Section: Extension Theoremsmentioning
confidence: 99%